Karl Popper's Falsification Theory of the Determination of the Gregorian Calendar Based on the Book of Risalatul Falakiyah K.H Misbachul Munir - Imroatul Munfaridah; Novi Fitia Maliha; Muh. Arif Royyani; Khalaf Mohamed Abdel Salam Bayumi (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2023)
The book of Risalatul Falakiyah is the work of KH. Misbachul Munir has a unique side compared to the Gregorian Calendar in general. This uniqueness is seen at the start of the calculation of the day and the market, namely Tuesday Pahing, while the count generally starts on Sunday Legi. This article aims to analyze the total of the Gregorian Calendar based on the book of Risalatul Falakiyah based on Karl Poper's falsification theory and analyze the accuracy of the comparison between the concept of calculating the Gregorian Calendar of the book of Risalatul Falakiyah using contemporary calculations based on technology. This research uses library research by conducting qualitative-descriptive analysis of data collected through documentation and interviews. The results showed: First, based on Karl Popper's falsification theory that the Gregorian calendar calculation theory of the book of Risalatul Falakiyah by K.H Misbachul Munir was proven by its correctness by comparing and testing its calculations with the standard formula of science obtained the same results. Second, based on the comparison and testing of technology-based calendar masehi calculations with mawaqit, it was found that the calendar calculation results from the book of Risalatul Falakiyah had the same accuracy as the calculation of mawaqit software.